A Pectic Polysaccharide from Codonopsis pilosula Alleviates Inflammatory Response and Oxidative Stress of Aging Mice via Modulating Intestinal Microbiota-Related Gut–Liver Axis - Zou, Yuanfeng; Yan, Hong; Li, Cenyu; Wen, Fang; Jize, Xiaoping; Zhang, Chaowen; Liu, Siqi; Zhao, Yuzhe; Fu, Yuping; Li, Lixia; Liu, Fan; Chen, Ji; et al. (Antioxidants, 2023)
Aging is a biological process that leads to the progressive deterioration and loss of physiological functions in the human body and results in an increase in morbidity and mortality, and aging-related disease is a major global problem that poses a serious threat to public health. Polysaccharides have been shown to delay aging by reducing oxidative damage, suppressing inflammatory responses, and modulating intestinal microbiota. Our previous studies have shown that polysaccharide CPP-1 extracted from the root of Codonopsis pilosula possesses noticeable anti-oxidant activity in vitro. Thus, in our study, we tested the anti-aging effect of CPP-1 in naturally aging mice (in vivo). Eighteen C57/BL mice (48-week-old, male) were divided into a control group, high-dose CPP-1 group (20 mg/mL), and low-dose CPP-1 group (10 mg/mL). We discovered that CPP-1 can exert a reparative effect on aging stress in the intestine and liver, including alleviating inflammation and oxidative damage. We revealed that CPP-1 supplementation improved the intestinal microbiota composition and repaired the intestinal barrier in the gut. Furthermore, CPP-1 was proved to modulate lipid metabolism and repair hepatocyte injury in the liver by influencing the enterohepatic axis associated with the intestinal microbiota. Therefore, we concluded that CPP-1 prevents and alleviates oxidative stress and inflammatory responses in the intestine and liver of aging mice by modulating the intestinal microbiota-related gut–liver axis to delay aging.